STUDI BUSANA PENGANTIN TRADISIONAL DI ALAM SURAMBI SUNGAI PAGU - Febrina, Febrina; Yasnidawati, Yasnidawati; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
Problem in this research is a traditional wedding dress in Alam Surambi Sungai Pagu with indicator (1) describe the original form of fashion traditional wedding dress (2) meaning of philosophical traditional wedding dress in Alam Surambi Sungai Pagu. (3) shape modification of the traditional wedding dress in Alam Surambi Sungai Pagu. The method used in this study is a qualitative method. Techniques of data through observations, interviews and documentation. The resultsare (1)traditional weddingat Alam Surambi Sungai Pagu, tofashionwedding dress of bride man are jacket, white shirt, longpants, the brideworeblackbasibaandsongket, accessoriesgroomwearIkek, fruitAua, weddingTakkondaiwomenwear, DressCords, GalangGadang, Tindiak, RingsandNails. MilinerisgroomKris, Salempang, hangingaskew, Pandiang, texstilyellow, sandalsorshoes, brideTokah, PinangCookcloth, sandals. (2) the meaning of philosophical traditional wedding dress in Alam Surambi Sungai Pagu generally containthe messagesandvalues ​​ofcultureandthe basicteachings of Islam. (3) Modified formofthe traditionalwedding dressin Alam Surambi Sungai Pagu adjustedmodrenisasibridalfashions, changes occur incoloranddecorationmaterials.